A behavioural dose-response model for migrating humpback whales and seismic air gun noise. (August 2018) - Dunlop, Rebecca A.; Noad, Michael J.; McCauley, Robert D.; Kniest, Eric; Slade, Robert; Paton, David; Cato, Douglas H.
Abstract: The behavioural responses of migrating humpback whales to an air gun, a small clustered seismic array and a commercial array were used to develop a dose-response model, accounting for the presence of the vessel, array towpath relative to the migration and social and environmental parameters. Whale groups were more likely to show an avoidance response (increasing their distance from the source) when the received sound exposure level was over 130 dB re 1 μPa 2 ·s and they were within 4 km of the source. The 50% probability of response occurred where received levels were 150–155 dB re 1 μPa 2 ·s and they were within 2.5 km of the source. A small number of whales moving rapidly close to the source vessel did not exhibit an avoidance response at the highest received levels (160–170 dB re 1 μPa 2 ·s) meaning it was not possible to estimate the maximum response threshold. Highlights: Humpback responses were indicative of avoidance to a non-threatening stimulus. The 50% response threshold was approximately 155 dB re 1 μPa 2 ·s and 2.5 km. Their response to seismic did not fit a classic sigmoidal dose-response curve. A large sample size was necessary to capture the behavioural variability.